Diagnostic Value of Magnetic Resonance Imaging Based Coracoid Morphology in Patients with Subscapularis Tears - Barış Acar; Hüseyin Buğra Altundal; Ekremcan Karaer; Ahmet Şenel; Ahmet Sinan Kalyenci; Engin Çarkçi ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2025)
Background: This study investigates the association between subscapularis tendon tears and the anatomical characteristics of the coracoid process, as assessed by magnetic resonance imaging (MRI) and to determine the predictive cut-off values for significant measurements.Methods: Patients who underwent surgery for rotator cuff injury between 2020 and 2024 were retrospectively reviewed. Those with a subscapularis tear were classified as Group 1, while those with an intact subscapularis were classified as Group 2. MRI images were analyzed to measure axial and sagittal coracohumeral distance (axCHD, sagCHD), coracoid overlap (CO), and coracoid angle (CA). The diagnostic utility of these parameters was assessed using receiver operating characteristic (ROC) curve analysis.Results: A significant association was found between subscapularis tear and axCHD, sagCHD, and CO measurements. Among these, sagCHD demonstrated the strongest predictive power, with an optimal threshold of 9.5 mm, a sensitivity of 77.8% and a specificity of 80.4%.Conclusion: Our study demonstrated that decreased axCHD and sagCHD, and increased CO, are associated with subscapularis tears. The intracoracoid angle, however, does not appear to influence the incidence of subscapularis tears.